Experiences of parents with an adolescent abusing substances admitted to a mental health institution in Giyani, South Africa - Evelyn N. Hlungwani; Nompumelelo Ntshingila; Marie Poggenpoel; Chris P.H. Myburgh (AOSIS, 2020)
Background: Substance abuse by adolescents may be a problem that contributes to their mental illness. Substance abuse does affect not only the individual who is abusing it but also friends, family and the whole community. The adolescent abusing substances may be mentally unstable and have unpredictable behaviour. There is no research on the experiences of parents with adolescents abusing substances in Giyani, South Africa. Objective: The purpose of the study was to explore and describe the experiences of parents with adolescents abusing substances admitted to a mental health institution in Giyani. Method: A qualitative, exploratory, descriptive and contextual research design was used. Data were collected by means of conducting individual, in-depth, phenomenological interviews, observations and field notes. The following central question was asked to the participants: 'How is it for you to have an adolescent who is abusing substances'. Data were analysed by using a thematic method of coding. An independent coder analysed data together with the researcher, and consensus was reached. Results: Four themes emerged from the data: parents experienced uncontrolled thoughts regarding their adolescent abusing substances, not being able to control their adolescent abusing substances through discipline, negative feelings regarding their adolescent abusing substances and negative consequences regarding their adolescents abusing substances. Conclusion: From the study result, it is clear that parents with adolescent abusing substances need professional assistance and support as evidenced by the challenges faced in terms of promoting, maintaining and restoring their mental health. Psychiatric nurses should take responsibility to educate the community about substance abuse, for example offering school health programmes. Further research studies can also be conducted in other villages to gain a greater understanding of those parents' experiences with an adolescent abusing substances.